2016
DOI: 10.5812/modernc.13000
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Gold Nanoparticles Using Barberry and Saffron Extracts

Abstract: Recently, synthesis of gold nanoparticles (AuNPs) is the subject of a lot of studies due to various applications in medicine, agriculture, and industry. The development of non-toxic and safe methods such as green chemistry to produce AuNPs is obviously recommended. In the current study, 2 antioxidant rich herbs of barberry and saffron stigma were applied as reducing agents for the 1-pot synthesis of size-controlled AuNPs. These AuNPs were characterized through ultraviolet-visible spectrophotometry (UV-vis), tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Then, to optimize the size and amount of synthesized GNPs, different concentrations of saffron extract (2-5 ml), HAuCl 4 (0.5-2.5 mM) and various temperatures (25°C-80 °C) were applied at different experimental times (from 1 h to 3 months). 32,38,39 In the experiments with different concentrations of the gold salt (0.5-2.5 mM), the highest absorbance of synthesized NPs was seen in the concentration of 1 mM and thus, it was considered as the optimal synthesis concentration (Figure 1(a)). Also, the sharp absorbance and stable particles were achieved at room temperature (Figure 1(b)).…”
Section: Synthesis and Characterization Of Gnp-extmentioning
confidence: 99%
“…Then, to optimize the size and amount of synthesized GNPs, different concentrations of saffron extract (2-5 ml), HAuCl 4 (0.5-2.5 mM) and various temperatures (25°C-80 °C) were applied at different experimental times (from 1 h to 3 months). 32,38,39 In the experiments with different concentrations of the gold salt (0.5-2.5 mM), the highest absorbance of synthesized NPs was seen in the concentration of 1 mM and thus, it was considered as the optimal synthesis concentration (Figure 1(a)). Also, the sharp absorbance and stable particles were achieved at room temperature (Figure 1(b)).…”
Section: Synthesis and Characterization Of Gnp-extmentioning
confidence: 99%
“…26 Abootorabi et al revealed the reduction of gold ions into GNP in a size controlled manner by 2 antioxidant rich herbs of barberry and saffron stigma extract using one step green synthesis method. 27 Almost 24 hr of reaction time was required at the temperature of 50°C and pH 7.5 to yield SPR band at 520 nm as shown in Figure 5b. Dudhane et al employed T. arjuna leaf extract for the environmentally friendly extracellular fabrication of metallic gold nanoparticles.…”
Section: Uv-vis-spectroscopy Analysis Of Gnp Synthesized Using Differ...mentioning
confidence: 99%
“…Green synthesis is an advanced method that uses natural reducing agents, plugs, and stabilizers surpassing the employment of toxic and expensive chemicals and high energy costs (Hussain et al, 2016). There is an increasing need for optimal eco-friendly and non-toxic methods of developing NPs such as gold NPs (AuNPs) preparation with CR (Hoshyar et al, 2016) and SF (Abootorabi et al, 2016). Solid lipid nanoparticles belong to the lipid nanotransporter family that can solubilize hydrophilic and lipophilic molecules in physiological environments.…”
Section: Nanoparticle Formulation and Green Synthesismentioning
confidence: 99%